Hội thảo khoa học về việc nghiên cứu và giảng dạy di sản văn hóa văn nghệ của Chủ tịch Hồ Chí Minh (Bộ Giáo dục và Đào tạo, 2013)
On May 12th 1989, Ministry of Higher Education opened the Conference about the study and the teaching of Ho Chi Minh's cultural and arterial works in universities.